xwixwi’em’: My Hul’q’umi’num’ story-telling journey - Seymour, George (2018)
Storytelling is an important tool for sharing knowledge across generations for Hul’q’umi’num’ people. Stories teach us about our way of life and our perspectives on how to be as First Nations peoples. In this project, I share two stories of the creature world that were told to me when I was still a boy. With the help of Elders, I brought to life versions in the Hul’q’umi’num’ language, a Coast Salish language of British Columbia. I discuss my journey to learn how to tell them in Hul’q’umi’num’. I give advice on structuring a story in terms of its organizational schema. I give examples of interesting ways to start a sentence in a story, avoiding the pitfall of English influence. Storytelling has proven to be an interesting path toward fluency. Stories are also an important way of documenting our language and providing resources for language teachers and learners.